Masjid Dato' Undang Kamat, Johol, Negeri Sembilan [lukisan teknik] - Ibrahim Mustaffa; Noriah Idris; Shahzaiham Sabarudin; Rusmini Abdul Rahman; Ho, Eric Fui Sen (Sekudai : UTM, 1995)
Kajian Lukisan Terukur (Jabatan Senibina) -Universiti Teknologi Malaysia, 1995